Answer:
(5, -2)
Explanation:
The equation of the ellipse is given by:
![$ ((x - h)^2)/(a^2) + ((y - k)^2)/(b^2) = 1 $](https://img.qammunity.org/2020/formulas/mathematics/college/v0o02bqcaw9vktfyoz6gd2yz5w2ej39yyg.png)
where
is the center of the ellipse.
The given equation of the ellipse is:
x² + 2y² - 10x + 8y + 25 = 0.
We have to reduce to the standard form so that we can compare and determine the center of the ellipse.
Subtracting
from the equation on both sides, we get:
x² - 10x + 2y² + 8y + 25 - 25 = - 25
![$ \implies x^2 - 10x + 2y^2 + 8y = - 25 $](https://img.qammunity.org/2020/formulas/mathematics/college/28u0q38aofjfy0kd811ceolphjp06b0vpz.png)
![$ \implies x^2 - 10x + 2(y^2 + 4y) = -25 $](https://img.qammunity.org/2020/formulas/mathematics/college/3hpj5a3qs0k897xmw1du9oic7ur8hc96ji.png)
The next step would be complete the squares. Let us complete
first.
![x^2 - 10x = x^2 - 5(2)x \\= x^2 - 5(2)x - 25 + 25 \\= (x - 5)^2 + 25](https://img.qammunity.org/2020/formulas/mathematics/college/ods4hjsi57szvs8iacop317hmfftqc7hui.png)
Now for
.
![2(y^2 + 4y) =2\{ y^2 + 2(2)y \} \\\\= 2\{y^2 + 2(2)y + 4 - 4 \} \\\\= 2\{(y + 2y)^2 - 4\} \\\\= 2\{(y + 2)^2\} - 8](https://img.qammunity.org/2020/formulas/mathematics/college/51p0qj0aurv798xbreyd5tkqavwhk9req9.png)
Therefore the equation becomes:
(x - 5)² + 2(y + 2)² = -25 + 25 + 8
⇒ (x - 5)² + 2(y - 2)² = 8
Since the
needs 1, we divide the entire equation by 8.
⇒
![$ ((x - 5)^2)/(8) + 2((y - 2)^2)/(8) = 1 $](https://img.qammunity.org/2020/formulas/mathematics/college/oeyjtzqp027ld9amowsq0isrf3th7omj2n.png)
![$ \implies ((x - 5)^2)/(8) + ((y + 2)^)/(4) = 1 $](https://img.qammunity.org/2020/formulas/mathematics/college/k0fehzsl916dp0hxn8h4f5ke6zll0zu5p1.png)
Comparing with standard form we get:
and
![$ (y - k)^2 = (y + 2)^2 $](https://img.qammunity.org/2020/formulas/mathematics/college/n0976wts26brhubxknc29150tldcn85pur.png)
⇒ (h,k) = (5,-2)
∴ The center of the ellipse is (5,-2).